Spontaneous Per Urethral Expulsion of Gossipibyoma - A Rarity - Muhammad Sajjad Ashraf; Ubaidullah Memon; Muhammad Talat Mehmood; Muhammad Shahab Athar Shahab Athar (Journal of the Dow University of Health Sciences, 2010)
Foreign bodies left accidentally during a surgical procedure are rare. In spite of careful intra-operative precautions andgauze counts mistake still occurs. Many of these cases present with sepsis, the foreign body may erode hollow viscerawith and without signs of peritonitis and discovered on laparatomy. These foreign bodies may remain silent for years.We are reporting an interesting case ofan11 years old girl who presents with gauze piece coming out ofher urethra 4years after cystolithotomy and right ureterolithotomy. Such cases of intraluminal migration and spontaneous expulsionof foreign body are rarely reported.